Editorial: Earth-affecting Solar Transients - Zhang, Jiaen (2018)
This Topical Collection (TC) is devoted to the recent advancement in the study of Earth-affecting solar transients. Earth-affecting solar transients encompass a broad range of phenomena, including major solar flares, coronal mass ejections (CMEs), interplanetary CMEs (ICMEs), solar energetic particle (SEP) events, and corotating interaction regions (CIRs). In the past decade, nearly continuous observations of the Sun and the inner heliosphere with an unprecedented wide spatial coverage from a fleet of spacecraft, including the Solar Terrestrial Relations ObservatoryAhead/Behind (STEREO A/B), the Solar Dynamics Observatory (SDO), the Solar and Heliospheric Observatory (SOHO), the Mercury Surface, Space Environment, Geochemistry, and Ranging (MESSENGER) spacecraft, Venus Express (VEX), the Advance Composition Explorer (ACE), and Wind, in combination with a significant development and improvement of global magnetohydrodynamics (MHD) numerical simulations and theoretical analyses, have greatly improved our understanding of solar transients and the prediction of their potential impact on Earth.